Digital Presence of Media in Oman: A Business Analytics Perspective - Farooque, Murtaza M. Junaid; Mohiuddin, Hamza; Aref, Mohammed; Rashed, Abdul; Khan, Mohammed Abdul Imran (Scientific Research, New Technologies and Applications Vol. 10, 2024)
The present paper studies the digital presence of Omani mass media houses from business analytics. It highlights the adoption of websites, social media platforms, and other online channels by these organizations. This gives valuable insight into the media landscape of Oman. The study examines web analytics data, including Alexa rankings, bounce rates, user time on websites, and visitor demographics. This analysis could offer insights into user engagement and the reach of these outlets. It uses web analytics, social media analytics and potentially other data sources to assess the digital performance of Omani media outlets.